Improving early nutritional intervention in hospitalised patients : laboratory test (prealbumin) versus routine clinical assessment : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Science, Nutrition and Dietetics at Massey University, Albany, Auckland, New Zealand - Eccles, Tracey (Massey University, 2013)
Malnutrition in hospitalised patients occurs in 30% of Australasian Hospitals. There are an estimated fifty malnutrition-screening tools currently available, although no single screening tool is universally accepted as gold standard in all settings. The Waitemata District Health Board (WDHB) hospitals: North Shore hospital (NSH) and Waitakere hospital utilise the Malnutrition Universal Screening Tool (MUST). A hospital dietitian audit performed in 2009 at NSH identified as few as 8% of patients were screened using MUST. Universal screening on hospital admission incorporating prealbumin has been proposed as a more effective method for early identification of patients at risk of diseaserelated malnutrition. Aims To evaluate whether universal prealbumin screening increases the number of patients identified and referred to a dietitian for comprehensive disease-related malnutrition assessment. Method A two-phase observational cohort study was conducted utilising consecutively admitted patients to: two acute surgical, one acute orthopaedic and two acute medical wards from February to April 2013. Phase I: Observational stage recorded dietetic inpatient referral data for patients screened by MUST triggering a dietetic referral. Phase II: Research protocol, patients were selected using electronic notes programme ConcertoTM. Patients that met the research inclusion criteria had admission blood samples tested for prealbumin and Creactive protein (CRP) within 36 hours post admission. The researcher examined whether abnormal prealbumin level <0.2 g/L triggered a prompt referral to a dietetic assessment. Dietetic inpatient referral data set was repeated for phase II as in phase I. Results Phase I, 970 patients were admitted during a 25-day control period. Patient referral pathway was either through MUST or clinical professional referral with 28% of patients having a completed MUST in their clinical notes, a total of 7.8% (76/970) of patients were referred. Phase II, 776 patients were admitted during a 22-day period, 564 patients met inclusion criteria and were selected for screening. Test results indicated 27% (155/564) had abnormal prealbumin results ranged from 0.03 g/L to 0.54 g/L; these patients deemed at risk of malnutrition. A total of 43 patients were referred to a dietitian through either MUST or clinical professional referral. 30% of those 43 patients assessed by a dietitian had abnormal prealbumin results, although 70% of those did not initiate a dietetic referral. Of 43 patients referred 51% had a completed MUST screen recorded; however nil patients referrals were triggered by abnormal prealbumin results. Conclusion In our study prealbumin results were found to be a sensitive marker of malnutrition risk with 27% of screened patients deemed at risk of malnutrition. This is in-line with international prevalence rates of hospital malnutrition set between 20-60%. However, despite ours findings it was identified that the clinicians poorly recognise hospital malnutrition, as patients were not referred based on abnormal pre-albumin levels.
Keywords: Malnutrition in hospitals; Hospital patient nutrition; Prealbumin; Malnutrition screening; Malnutrition Universal Screening Tool (MUST); Malnutrition screening tool